Determinants of Business Survival and Success of SMEs: A Study on Kadazandusun Businesses - Suffian Koroh, Tina (2007)
The purpose of this dissertation is to investigate and gain a deeper understanding of the survival and success of SMEs specifically on the Kadazandusun businesses by looking into the challenges that they face and the determinants in which they believed contribute towards business survival and success. As this dissertation is in a form of exploratory study, the case study method was selected whereby data was collected by reviewing existing literature and conducting semi-structured interviews. The interviews were conducted with Kadazandusun SMEs’ owners within any industry in Sabah. Using qualitative and quantitative analysis approaches, findings show that these SMEs face problems in terms of human resource, finance, and competition. Consequently, personal characteristics, proper handling of management, and building good relationships emerge as ways to survive and succeed in the marketplace. The findings are only based on a very small sample and are not particular to any industry. Nevertheless, findings may produce interesting suggestions of conducting research involving outside parties for a more significant generalisation and of other indigenous groups for meaningful comparison.